2003
DOI: 10.1038/sj.ejhg.5201111
|View full text |Cite
|
Sign up to set email alerts
|

Provision of genetic services in Europe: current practices and issues

Abstract: This paper examines the professional and scientific views on the social, ethical and legal issues that impact on the provision of genetic services in Europe. Many aspects have been considered, such as the definition and the aims of genetic services, their organization, the quality assessment, public education, as well as the partnership with patients support groups and the multicultural aspects. The methods was primarily the analysis of professional guidelines, legal frameworks and other documents related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 59 publications
2
59
0
Order By: Relevance
“…In the older literature about half of the articles that mentioned a solution suggested involving patients in the process of recontacting. 1,7,10,12,18,21,23,25 Patients could contribute by, for example, contacting the department regularly to inquire about new genetic information, keep the genetics department up to date regarding address and personal information, and checking for new genetic developments on websites. Fitzpatrick et al 12 suggested including informing the media, support groups, and other health professionals in the recontacting process.…”
Section: Recontact In Clinical Genetics: Practical Barriers and Solutmentioning
confidence: 99%
“…In the older literature about half of the articles that mentioned a solution suggested involving patients in the process of recontacting. 1,7,10,12,18,21,23,25 Patients could contribute by, for example, contacting the department regularly to inquire about new genetic information, keep the genetics department up to date regarding address and personal information, and checking for new genetic developments on websites. Fitzpatrick et al 12 suggested including informing the media, support groups, and other health professionals in the recontacting process.…”
Section: Recontact In Clinical Genetics: Practical Barriers and Solutmentioning
confidence: 99%
“…This often involves several visits to a genetics clinic to undergo genetic counseling and physical evaluation, receive genetic test results, and attend follow-up appointments. In Europe and the United States, access to genetics services is often available only in urban centers, 18,19 which means that remote populations may not have access to the information, treatment, and psychosocial support that genetics services can offer. The potential for using telemedicine in clinical genetics service delivery has been highlighted by a number of authors, [19][20][21] who have suggested that it may enable more equitable access to genetics services for people who must otherwise travel long distances to specialist centers.…”
mentioning
confidence: 99%
“…In Europe and the United States, access to genetics services is often available only in urban centers, 18,19 which means that remote populations may not have access to the information, treatment, and psychosocial support that genetics services can offer. The potential for using telemedicine in clinical genetics service delivery has been highlighted by a number of authors, [19][20][21] who have suggested that it may enable more equitable access to genetics services for people who must otherwise travel long distances to specialist centers. Indeed, an increasing number of studies are exploring alternative models of service provision, including genetic counseling over the telephone, 22,23 and genetics consultations via real-time videoconferencing, 24 so as to improve equality of access, improve cost efficiency, and help to meet the increasing demand for these services.…”
mentioning
confidence: 99%
“…This document provides a reflection on the paradigm shift in the field of human genetics from rare monogenic to common disorders with a genetic component. It continues a tradition of documents and initiatives that were set up to assess and harmonize genetic testing services in Europe (Godard et al 2003); (Ibarreta et al 2004); (Cassiman 2005). This first background document led to the second document: recommendations that aim "to reflect the view of the European human genetics scientific and professional community" on genetic testing and common disorders in a public health framework at that moment (van El et al 2011).…”
Section: Introductionmentioning
confidence: 99%